STRATEGIC MANAGEMENT IN ISLAMIC EDUCATION: A CASE STUDY OF CAHAYA BANGSA ISLAMIC BOARDING SCHOOL - Muhammad Musip; Lutfi Khaer; Yus’an; Titiek Rohanah Hidayati; Erma Fatmawati (Politea : Jurnal Politik Islam, 2026)
This study aims to analyze the internal and external environments and examine the implementation of strategic management at Cahaya Bangsa Islamic Boarding School, East Lombok, in responding to the challenges of the global era. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving five key informants, including institutional leaders, teachers, administrative staff, and parents. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing, supported by SWOT analysis. The findings reveal that the institution’s internal environment demonstrates strong commitment from human resources and an organizational culture grounded in Islamic values. However, weaknesses remain in management systems and technological integration. The external environment presents opportunities, particularly the increasing public demand for Islamic education, but also poses challenges such as institutional competition and rapid technological advancement. The study further shows that strategy formulation has integrated Islamic values with global competencies, although it has not been fully based on systematic strategic analysis. Strategy implementation has been carried out through various academic and non-academic programs, yet it is constrained by coordination issues and limited resources. Meanwhile, strategy evaluation is conducted periodically but has not yet been supported by measurable performance indicators. This study concludes that the effectiveness of strategic management depends on the institution’s ability to integrate strategic environmental analysis with systematic implementation. Therefore, strengthening analytical approaches and developing performance-based evaluation systems are essential to enhance the competitiveness of Islamic educational institutions in the global era.